1996
DOI: 10.1007/bf02532343
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNAs for neurotrophic factors (NGF, BDNF, NT-3, and GDNF) and their receptors (p75 ngfr , TrkA, TrkB, and TrkC) in the adult human peripheral nervous system and nonneural tissues

Abstract: The steady-state mRNA levels of the four neurotrophic factors of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3) and glial cell line-derived neurotrophic factor (GDNF) and their receptors (p75NGFR, trkA, trkB and trkC) in the adult human peripheral nervous system (PNS) as well as nonneural tissues were examined using quantitative reverse transcription-polymerase chain reaction (RT-PCR). NGF and BDNF mRNA levels were high in the heart and spleen as well as in the dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
1
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(204 citation statements)
references
References 82 publications
11
188
1
4
Order By: Relevance
“…Glial cell line-derived neurotrophic factor is a novel member of the transforming growth factor family and is reported to exhibit trophic factor on embryonic substantia nigra dopaminergic neurons in vitro and possibly in vivo. 1,3,7,9,16,19,20 It may qualify as a highly specific dopaminergic neurotrophic factor with potential therapeutic benefit in the treatment of PD, a neurodegenerative disorder characterized by the loss of dopaminergic neurons in substantia nigra. For these reasons, it is suggested that GDNF exerts long-lasting trophic effects on dopaminergic neurons in vivo and may be useful as a potential therapeutic agent in individuals suffering from PD.…”
Section: Discussionmentioning
confidence: 99%
“…Glial cell line-derived neurotrophic factor is a novel member of the transforming growth factor family and is reported to exhibit trophic factor on embryonic substantia nigra dopaminergic neurons in vitro and possibly in vivo. 1,3,7,9,16,19,20 It may qualify as a highly specific dopaminergic neurotrophic factor with potential therapeutic benefit in the treatment of PD, a neurodegenerative disorder characterized by the loss of dopaminergic neurons in substantia nigra. For these reasons, it is suggested that GDNF exerts long-lasting trophic effects on dopaminergic neurons in vivo and may be useful as a potential therapeutic agent in individuals suffering from PD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their effects in neural survival and differentiation, neurotrophins are now implicated in neurite outgrowth, synaptic plasticity, cell cycle control and apoptosis during adulthood (Schinder and Poo, 2000;Chao, 2003). Furthermore, recent data show that neurotrophins are involved in a variety of biological processes in nonneuronal tissues in humans and other vertebrates (Yamamoto et al, 1996;Sariola, 2001;Leon et al 1994;Rosenbaum et al 1998;Tessarollo, 1998).…”
Section: ©2008 European Journal Of Histochemistrymentioning
confidence: 99%
“…4). NGFR, within the liver, has been found on stellate cells (27,28), which prompted us to further investigate desmin expression, an intracytoplasmic protein found in hepatic stellate cells (29).…”
Section: Suskind Cd34 + Ck7/8 + Cells In the Fetal Liver Page 11 Of 26mentioning
confidence: 99%
“…Hepatic stellate cells have been shown to be an source of several neurotrophins and express neurotrophin receptors (27,28,39). Although hepatocytes may express low levels of NGFR (40), no other liver cell has been reported to have high expression.…”
Section: Suskind Cd34 + Ck7/8 + Cells In the Fetal Liver Page 11 Of 26mentioning
confidence: 99%